2021
DOI: 10.1111/cts.13158
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic/pharmacodynamic assessment of imipenem/cilastatin/relebactam in patients with hospital‐acquired/ventilator‐associated bacterial pneumonia

Abstract: In the phase III RESTORE‐IMI 2 study (ClinicalTrials.gov: NCT02493764), the combination antibacterial agent imipenem/cilastatin/relebactam (IMI/REL) demonstrated noninferiority to piperacillin/tazobactam for the end points of all‐cause mortality at day 28 and favorable clinical response at the early follow‐up visit in adult participants with gram‐negative hospital‐acquired bacterial pneumonia/ventilator‐associated bacterial pneumonia (HABP/VABP). Existing population pharmacokinetic models for imipenem (IPM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Of these isolates, the MIC of 1 K. pneumoniae isolate and 1 S. marcescens isolate was 2 μg/mL, which is considered intermediate susceptibility according to the CLSI breakpoint for IMR (MIC of 2 μg/mL). However, it has been reported that at the recommended IMI/REL dosing regimens, >90% of patients were predicted to achieve joint pharmacokinetic/pharmacodynamic targets at an MIC breakpoint of ≤2 μg/mL, which aligns with the European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoint for IMR ( 16 , 17 ). Taking this into consideration, IMR may be effective for 2/3 and 2/2 of imipenem-nonsusceptible isolates of K. pneumoniae and S. marcescens collected in this study, respectively, and thus, these isolates would be considered susceptible by EUCAST breakpoints but of intermediate susceptibility by CLSI breakpoints.…”
Section: Discussionmentioning
confidence: 93%
“…Of these isolates, the MIC of 1 K. pneumoniae isolate and 1 S. marcescens isolate was 2 μg/mL, which is considered intermediate susceptibility according to the CLSI breakpoint for IMR (MIC of 2 μg/mL). However, it has been reported that at the recommended IMI/REL dosing regimens, >90% of patients were predicted to achieve joint pharmacokinetic/pharmacodynamic targets at an MIC breakpoint of ≤2 μg/mL, which aligns with the European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoint for IMR ( 16 , 17 ). Taking this into consideration, IMR may be effective for 2/3 and 2/2 of imipenem-nonsusceptible isolates of K. pneumoniae and S. marcescens collected in this study, respectively, and thus, these isolates would be considered susceptible by EUCAST breakpoints but of intermediate susceptibility by CLSI breakpoints.…”
Section: Discussionmentioning
confidence: 93%
“…PK/PD methodology previously described. 28 MIC of 2 µg/mL is EUCAST breakpoint for Enterobacterales and P. aeruginosa . 32 NRF, normal renal function.…”
Section: Resultsmentioning
confidence: 99%
“…Existing population PK models for concentration–time profiles for imipenem and relebactam were updated using data from the RESTORE-IMI 2 study; 28 simulations were performed to calculate the PK/PD joint PTA (unbound or free drug levels above PK/PD targets) and to confirm current dosing schedules in patients with variable renal function and HABP/VABP. The details of model development, validation and qualification, as well as the virtual population pool used for the Monte Carlo simulations, which included 1000 patients with HABP/VABP in each renal category, have been previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide information on the optimal drug dosing according to PK/PD data, which are then validated in clinical practice through phase 3 studies. 10 , 11 …”
mentioning
confidence: 99%